(untitled) (The Journal of Medicine, Humanity and Media, 2025)
Health communication research, originating from Western academic traditions, has long been a blend of various academic discourses. In the context of Chinese academia, these studies have undergone theoretical transfer and adaptation, completing the migration of discourse fields and subsequently rejuvenating theoretical vigor. Against this background, this research, utilizing the framework of knowledge archaeology, conducts an academic historical review of the discourse system in Chinese health communication research. The research shows that in the evolution of discourse, hospital topics have gradually shifted from a loss of focus to a refocused attention, reflecting the challenges and achievements encountered in the gradual construction of an independent knowledge system within Chinese health communication research. To construct a health communication research knowledge system with local characteristics, it is crucial to enhance the focus on local issues and transcend disciplinary boundaries.